We have to find f(3) given that f(3x) + 3*f(-3x) = x + 1

f(3x) + 3*f(-3x) = x + 1

for x = 1

=> f(3) + 3*f(-3) = 1 + 1 = 2 ...(1)

for x = -1

=> f(-3) + 3*f(3) = 0 ...(2)

(1) - 3*(2)

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to find f(3) given that f(3x) + 3*f(-3x) = x + 1

f(3x) + 3*f(-3x) = x + 1

for x = 1

=> f(3) + 3*f(-3) = 1 + 1 = 2 ...(1)

for x = -1

=> f(-3) + 3*f(3) = 0 ...(2)

(1) - 3*(2)

=> f(3) + 3*f(-3) - 3*f(-3) - 9*f(3) = 2

=> f(3) - 9*f(3) = 2

=> -8*f(3) = 2

=> f(3) = -1/4

**The required value of f(3) = -1/4**